A randomized controlled trial of training in Motivational Interviewing for child protection. (May 2018) - Forrester, Donald; Westlake, David; Killian, Mike; Antonopoulou, Vivi; McCann, Michelle; Thurnham, Angela; Thomas, Roma; Waits, Charlotte; Whittaker, Charlotte; Hutchison, Dougal
Abstract: There has been interest in developing more evidence-based approaches to child and family social work in the UK in recent years. This study examines the impact of a skills development package of training and supervision in Motivational Interviewing (MI) on the skills of social workers and the engagement of parents through a randomized controlled trial. All workers in one local authority were randomly assigned to receive the package ( n = 28) or control ( n = 33). Families were then randomized to trained ( n = 67) or untrained ( n = 98) workers. Family meetings with the worker shortly after allocation were evaluated for MI skill. Research interviews gathered data including the Working Alliance Inventory (WAI). Follow-up interviews 20 weeks later repeated the WAI, and other outcome measures including Goal Attainment Scaling (GAS) and rating of family life. Between group analysis found statistically significant difference in MI skills, though these was not substantial (2.49 in control, 2.91 MI trained, p = .049). There was no statistically significant difference between groups in any other outcome measures. The package of training and supervision did not create sufficient increase in MI skills to influence engagement or outcomes. Implications for understanding the relationship between skills, engagement and organizational change are discussed.